Eksplorasi Media Pembelajaran Cimpa Unung Terhadap Peningkatan Numerasi Volume Tabung Di Kelas VII SMPS Budi Murni Pintu Angin - Togatorop, Fresty Handayani; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the utilization of Cimpa Unung, a traditional food of the Karo ethnic group, as a contextual learning media to enhance the numeracy skills of seventh-grade students on the topic of cylinder volume at SMPS Budi Murni Pintu Angin. The background of this study is based on the low mathematics achievement caused by the dominance of lecturing methods without support from concrete and engaging learning media. The approach used in this research is qualitative exploratory, employing data collection techniques such as observation, structured interviews, and documentation. The participants consisted of 30 seventh-grade students as primary informants and a mathematics teacher as a supporting informant. The results revealed that using Cimpa Unung as a learning media provides students with a more tangible and practical learning experience. Through hands-on practice with this media, students are better able to understand the concept of cylinder volume and apply basic mathematical formulas in real-life contexts. Furthermore, this media helps students analyze data, make predictions, and take decisions based on their analysis. Learning with Cimpa Unung not only improves understanding of mathematical concepts but also makes the learning process more engaging and meaningful. Therefore, Cimpa Unung can be considered an effective and relevant alternative learning media while also utilizing local cultural values in mathematics education at school.